Allelopathic and phytochemical potential of the aqueous extract of Curcuma longa L.: contributions to the production of bioherbicides - Silva, Leonardo Mendes da; Matilde, Marcela Emiliano Novaes; Silva, Fábio Junio da (Revista de Ciências Agroveterinárias, 2024)
The plant Curcuma longa L. is rich in bioactive compounds. However, there are few available studies that have investigated its allelopathic activity. In this work, we sought to preliminarily investigate the main chemical groups with allelopathic and bioherbicide activity present in the aqueous extract obtained from the rhizomes of C. longa, as well as its effect on the germination and initial growth of lettuce (Lactuca sativa L.) and wheat (Triticum aestivum L.) seedlings. Phytochemical analysis was performed using precipitation and colorimetric techniques. To determine the allelopathic potential of the extract, seven concentrations (1 to 64 g L-1) were tested, in addition to two control groups: distilled water (negative control) and glyphosate (positive control). The seeds remained in contact with the different concentrations for 72 hours. The evaluated parameters were: germination percentage (GP), germination speed index (GSI), root and shoot length of the seedlings, and median inhibitory concentration (IC50). Four compounds with allelopathic potential were identified: alkaloids, steroids, flavonoids, and terpenes. The results of the biological assay revealed that the aqueous extract had a limited impact on GP, showing effects only at the highest concentration (64 g L-1), causing a reduction of 20.70% in this parameter in both species. Additionally, it was found that the germination speed index (GSI) was significantly influenced by concentrations higher than 4 g L-1 for both species. The length of the root and shoot of the seedlings decreased with increasing doses. Shoot length was the most sensitive parameter, with an IC50 of 3.73 and 7.20 g L-1 required for wheat and lettuce, respectively. The results suggest that the extract of this plant has potential for the production of post-emergence bioherbicides.